ANALISIS EFISIENSI USAHA ALUMINIUM CUSTOM DI KOTA PEKANBARU - Abdul Latif; Deny Setiawan; Indri Yovita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2026)
This study aims to determine the amount of income of aluminum industry producers inPekanbaru, as well as the level of efficiency of the business being run. The method used is aquantitative descriptive method, with a case study approach on six aluminum business units. Thedata used includes primary data obtained through observation, interviews, and questionnaires, aswell as secondary data from related agencies. Data analysis was carried out by calculating totalproduction costs (Total Cost/TC), total revenue (Total Revenue/TR), net income (π = TR – TC), andbusiness efficiency (R/C Ratio = TR/TC). The results of the study indicate that the total productioncosts of woodworking producers range from Rp 131,020,000 to Rp 184,340,000 per year, withtotal revenue between Rp 402,600,000 to Rp 714,000,000 per year. The net income obtainedranges from Rp 265,630,000 to Rp 578,380,000 per year. The average R/C ratio was 3.56,indicating that the aluminum business in Pekanbaru is considered efficient and feasible, as allproducers are profitable (R/C 1). This research is expected to provide consideration forbusiness actors and local governments in developing the small a'nd medium-sized industry sector,particularly in the aluminum sector. Keywords: Aluminum Business, Aspect Of The Market Revenue, Production Costs, FeasibilityStudy